Report of the Steering Committee on Communications and Information For The Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2002)
The Report of the Steering Committee on Communications and Information for the Tenth Five-Year Plan (2002–2007), constituted by the Planning Commission under the chairmanship of N. K. Singh, outlines a comprehensive strategy for transforming India’s communications and information sectors into globally competitive, technology-driven engines of economic growth. Recognizing the pivotal role of Information and Communication Technology (ICT) in wealth generation, employment creation, and governance reform, the report emphasizes the development of world-class telecommunications infrastructure at affordable rates, particularly to support India’s comparative advantage in Information Technology and IT-enabled services. It reviews the significant expansion achieved during the Ninth Plan, including rapid growth in fixed and cellular networks, corporatization of the Department of Telecommunications into Bharat Sanchar Nigam Limited, strengthening of regulatory frameworks through the establishment of the Telecom Regulatory Authority of India, and progressive liberalization measures such as opening national and international long-distance services, internet telephony, and infrastructure provision to competition. The report highlights emerging trends including rapid cellular growth, declining equipment costs, expansion of data services, broadband requirements, rural connectivity gaps, universal service obligations, and technological convergence across telecom, IT, broadcasting, and media sectors. It advocates an integrated policy approach based on convergence and e-governance, structural reforms to foster competition and level playing fields, efficient spectrum management, enhanced research and development, and safeguards for national security interests. The overarching objective of the Tenth Plan is to ensure affordable and effective communication access to all citizens, accelerate rural penetration, promote transparency and efficiency in governance through ICT, and position Indian telecom enterprises as global players, thereby enabling balanced and knowledge-driven economic development.
Government of India Planning Commission May, 2002
Keywords: Communications And Information Sector; Tenth Five-Year Plan; Information And Communication Technology; Telecommunications Reform; E-Governance; Telecom Liberalization; Universal Service Obligation; Broadband Expansion; Convergence Policy; Telecom Regulatory Authority Of India; Bharat Sanchar Nigam Limited; Information Technology Enabled Services